Studies on combining ability and gene action for heat stress tolerance traits in Indian mustard (Brassica juncea L.) - Bhagirath Ram; Priyamedha; HS Meena; Arun Kumar; BK Singh; Reema Rani; Anil Kumar; KH Singh; PK Rai (Journal of Oilseed Brassica, 2026)
In order to identify parents for suitable use in a breeding programme for development of high yielding varieties of Indianmustard with heat stress tolerant traits, the combining ability and gene action for certain physiological traits wereinvestigated in half-diallel crossings among eight parental lines. The cultivars investigated were NRCHB 101, GM-2,NRCDR-601, BPR-543-2, BPR-549-9, JN-032, Urvashi and BPR-541-2 possess different tolerance levels to heat stress.Heat stress conditions were achieved through early sowing under conserve moisture condition. On the date of seeding(September, 28) of the year 2013-14, the maximum soil temperature at 0- 10 cm depth was 39.0oC. Data were subjected toanalysis of variance and combining abilities factor analysis. Analysis of variance for general combining ability (GCA)and specific combining ability (SCA) displayed significant general and specific combining effects for the seven seedyield and physiological traits i.e. population survival (%) 10 DAS, population survival (%) 25 DAS, membrane stabilityindex (%), excised- leaf water loss (%), relative water content (%), water retention capacity of leaves (%) 24hrs and seedyield per plant (g). For all the traits the GCA effects were relatively more important than the SCA effects, indicating thatadditive genetic effects were predominant. Crosses displaying high SCA effects for relative water content (%), membranestability index (%) and seed yield per plant (g) were observed to be derived from parents having various types of GCAeffects (high x high, high x low, low x low and medium x low).The single seed descent method can be applied to exploitadditive gene effects whereas dominance gene effects could be valuable in hybrid mustard breeding programmes.Among the parents, genotypes BPR-549-9, BPR-543-2 and Urvashi were found to be superior general combiners for seedyield and heat stress tolerance traits. Likewise, crosses involving diverse parents showed significant SCA effects forseed yield and other heat stress tolerance traits.